CORRIGENDUM: Microbiological landscape and parameters of antibiotic resistance of pathogens in patients of neonatal intensive care units [Pharmacy & Pharmacology. 2024;12(6):378-393. DOI: 10.19163/2307-9266-2024-12-6-378-393] - O. I. Butranova; A. A. Gorbacheva; S. K. Zyryanov; O. G. Ni (Фармация и фармакология (Пятигорск), 2025)
Referred to by: Butranova O.I., Gorbacheva A.A., Zyryanov S.K., Ni O.G. Microbiological landscape and parameters of antibiotic resistance of pathogens in patients of neonatal intensive care units. Pharmacy & Pharmacology. 2024;12(6):378-393. https://doi.org/10.19163/2307-9266-2024-12-6-378-393We hereby inform readers that in the final version of the article changes were made in Russian and English.In the published article “Microbiological landscape and parameters of antibiotic resistance of pathogens in patients of neonatal intensive care units”, there was an error. In the authors' affiliations did not include all institutions and positions held: Butranova O.I. – Research Fellow of IPCE RAS, Moscow, Russia; Gorbacheva A.A. – Research Engineer IPCE RAS, Moscow, Russia; Zyryanov S.K. – Chief Research Fellow of IPCE RAS, Moscow, Russia.Correct version:O.I. Butranova1,2, A.A. Gorbacheva1,2,3, S.K. Zyryanov1,2,4, O.G. Ni31 Peoples’ Friendship University (RUDN University),6 Miklukho-Maklaya Str., Moscow, Russia, 1171982Institute of Physical Chemistry and Electrochemistry of Russian Academy of Sciences,bldg. 4, 31, Russia, Leninsky Prospekt, Moscow, 1190713 Kommunarka Center,8/3 Sosenskiy Stan Str., Moscow, Russia, 1088144 City Clinical Hospital No. 24,10 Pistsovaya Str., Moscow, Russia, 127015 О.И. Бутранова1,2, А.А. Горбачева1,2,3, С.К. Зырянов1,2,4, О.Г. Ни31Федеральное государственное автономное образовательное учреждение высшего образования «Российский университет дружбы народов имени Патриса Лумумбы»,Россия, 117198, г. Москва, ул. Миклухо-Маклая, д. 62 Федеральное государственное бюджетное учреждение науки Институт физической химии и электрохимии им. А.Н. Фрумкина Российской академии наук,Россия, 119071, г. Москва, Ленинский проспект, д. 31, корп. 43 Государственное бюджетное учреждение здравоохранения города Москвы «Московский многопрофильный клинический центр «Коммунарка»Департамента здравоохранения города Москвы»,Россия, 108814, г. Москва, ул. Сосенский Стан, д. 8/34 Государственное бюджетное учреждение города Москвы «Городская клиническая больница № 24 Департамента здравоохранения города Москвы»,Россия, 127015, г. Москва, ул. Писцовая, д. 10 AUTHORSOlga I. Butranova – Candidate of Sciences (Medicine), Assistant Professor of the Department of General and Clinical Pharmacology of the Medical Institute, Peoples' Friendship University (RUDN University); Research Fellow of IPCE RAS. ORCID ID: 0000-0001-7729-2169. E-mail: butranova-oi@rudn.ruAnastasiia A. Gorbacheva – Assistant Lecturer of the Department of General and Clinical Pharmacology of the Medical Institute, Peoples' Friendship University (RUDN University); Research Engineer IPCE RAS;  Clinical Pharmacologist of Kommunarka Center (Moscow, Russia). ORCID ID: 0009-0003-9721-6931. E-mail: gorbacheva_aa@pfur.ruSergey K. Zyryanov – Doctor of Sciences (Medicine), Professor, Head of the Department of General and Clinical Pharmacology of the Peoples' Friendship University (RUDN University); Chief Research Fellow of IPCE RAS; Deputy Chief Physician of the City Clinical Hospital No. 24 (Moscow, Russia). ORCID ID: 0000-0002-6348-6867. Е-mail: zyryanov_sk@rudn.universityOksana G. Ni – Head of the Department of Clinical Pharmacology of the Kommunarka Center (Moscow, Russia). ORCID ID: 0000-0003-0994-0579. E-mail: ni.oksana@gmail.com Due to a technical error on part and without any malicious intent, it was stated in the "Funding" section that "This study did not have financial support from third-party organizations."The authors regret that the following statement was missed out due to oversight in the Funding section in the version of this article initially published: "The research was carried out at the expense of the Russian Science Foundation No. 23-73-30004, https://rscf.ru/project/23-73-30004 /".Correct version:FUNDINGThe research was carried out at the expense of the Russian Science Foundation No. 23-73-30004, https://rscf.ru/project/23-73-30004/ The error does not change the essence of the data presented in the article, does not violate their perception by readers or interpretation.The authors would like to apologize for any inconvenience caused. The authors declare no conflict of interest.The original article has been updated in online-version: https://www.pharmpharm.ru/jour/article/view/1667